General practice management of chronic post-surgical pain in patients with hip fracture: a qualitative study - Cao, Wenshu; Ye, Jizhong; Yan, Yini; Xu, Cheng; Lv, Qiwei (Frontiers in Medicine, 2024)
BACKGROUND: Hip fractures are common among elderly people and often lead to chronic post-surgical pain (CPSP). Effective CPSP management when patients transition from hospital to community settings is essential, but has not been sufficiently researched. This study examined general practitioner (GP) perspectives on managing patients with CPSP after hip fractures in Shanghai, China. METHODS: A descriptive qualitative study was performed wherein semi-structured interviews were conducted with GPs practicing in Shanghai who volunteered to participate. This study was initiated after a regional survey of general practice care for patients with CPSP following hip fracture. RESULTS: Six key themes emerged: (1) GPs’ care priorities for patients with CPSP varied; (2) pharmacological management posed challenges in terms of selecting appropriate medications; (3) consultation time constraints hindered comprehensive management; (4) GPs desired better communication from hospitals at discharge; (5) limited access to services, such as pain specialists and allied health, obstructed optimal care delivery; and (6) patient nonadherence to CPSP treatment was an issue. CONCLUSIONS: Multiple patient-, provider-, and system-level factors affected GP care for patients with CPSP after hip fracture. Improved interdisciplinary communication and education on evidence-based CPSP guidelines are needed to address the knowledge gaps among GPs. Barriers to healthcare access must be minimized to facilitate guideline-based care.